KEMAMPUAN ASESMEN GURU TAMAN KANAK-KANAK DI KECAMATAN LUBUK SIKAPING - Dara Mulyana, Dhinka; Mahyuddin, Nenny; Rakimahwati; Yaswinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In learning evaluation as part of the educational process, teacher assessment skills are a crucial competency required to optimize student assessment. This study aims to determine the assessment skills of kindergarten teachers in Lubuk Sikaping District. The research method used was descriptive quantitative research, with data collection using a questionnaire administered to a sample of 35 kindergarten teachers in Lubuk Sikaping District. The findings indicate that teachers' ability to implement learning assessments is in the high category (>80%). This level of achievement is achieved through the planning, implementation, processing, and utilization stages. Teachers are able to plan learning assessments, implement learning assessments using assessment techniques, process and analyze assessment results, and utilize assessment results for follow-up learning. This indicates that teachers understand the basic concepts of assessment and can apply them to learning activities in kindergarten. However, it is recommended that teachers continuously improve their assessment competencies to support the quality of learning and optimal early childhood development.